Pengembangan Media Pembelajaran Berbasis Powtoon Bermuatan Karakter terhadap Kemampuan Berpikir Kritis pada Materi Sistem Persamaan Linear Dua Variabel - Dewi Safariani; Muchtadi Muchtadi; Dewi Risalah (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to produce powtoon-based learning video learning media to improve students' critical thinking skills in class VIII two-variable linear equation system (SPLDV) material at SMPN 2 Putussibau which achieves a level of validity, practicality, and efficiency. This research method uses research and development involving 3 material validator experts and 3 media validator experts. The subjects of this study were grade VIII students of SMPN 2 Putussibau totaling 14 students. Data collected validation sheets, student response questionnaires, teacher response questionnaires, and tests of students' critical thinking skills. The results of this study showed that the learning video media assessed validity 86% (very valid), practical assessment 84% (very practical) and effectiveness assessment 85.7% (very effective). So, it can be stated that animated videos are suitable to be used as learning media for grade VIII SMPN 2 Putussibau regarding the subject of Two Variable Linear Equation System (SPLDV).